18S and 28S rDNA identity and phylogeny of two novel myxosporeans infecting gills of cyprinid carps inhabiting a cold water wetland in northern India. (July 2018) - Gupta, Aditya; Kaur, Harpreet
Abstract: The sequences of 18S and 28S rDNA have been extensively used as molecular markers to resolve phylogenetic relationships among various myxosporeans infecting fishes. Two novel myxosporeans have been identified during the present study namely, Henneguya latiusii sp. nov. infecting gills of Crossocheilus latius and Myxobolus atkinsoni sp. nov. infecting gills of Labeo rohita inhabiting Ranjit Sagar Wetland, Punjab (India). These myxosporeans formed plasmodia in the gill arch and gill lamellae respectively and infection was moderate (gill plasmodium index, GPI: 2). Myxospores of both the species possessed distinct morphological and morphometric characteristics hence validated as new species. Phylogenetically, H. latiusii sp. nov. was closest to H. doneci infecting gill filaments of Carassius auratus gibelio, with 96% and 74% similarity in 18S and 28S rDNA respectively. Similarly, M. atkinsoni sp. nov. showed close homogeneity of 90% with M. turpisrotundus and 83% with M. nielii infecting gills of Carassius auratus . The phylogenetic analyses of species of Myxobolus and Henneguya showed a tendency to cluster according to the order or family of the host, tissue and geographical location. This study is the first report on LSU gene marker (28S rDNA) standardized on myxozoans infecting fresh water fishes from Indian subcontinent. Graphical abstract: Image 1 Highlights: Two noval myxosporeans i.e. Henneguya latiusii infecting gill arch of Crossocheilus latius and Myxobolus atkinsoni infecting gill lamellae of Labeo rohita has been described on the basis of morphology, 18S and 28S rDNA sequences and analyzed phylogenetically. The phylogenetic tree showed the paraphyletic nature of Henneguya and Myxobolus genera showing a close similarity between the two. The present study also showed that the phylogenetic analyses of the Myxobolus and Henneguya parasites of fishes have a tendency to cluster according to the order or family of the host, tissue and geographical location. This study is the first report on LSU gene marker (28S rDNA) standardized on myxozoa from the Indian subcontinent.